Little Burro - Arnosky, Jim (New York, NY : G.P. Putnam's Sons, an imprint of Penguin Group (USA) Inc., 2013)
"When Little Burro's band of burros leaves her canyon, Little Burro does not want to follow, but she soon finds out that visiting new places can be fun"--
Keywords: Donkeys -- Juvenile fiction; Donkeys -- Fiction